Pengggunaan Metode Creative Problem Solving Dalam Meningkatkan Kemampuan Berpikir Kritis Bagi Siswa Pada Pembelajaran IPA - Ida Juliani; Akmal Ramadhan; Dian Anggraeni Maharbid (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2023)
Students' lack of critical thinking abilities is a result of a learning process that is still teacher-centered and provides them with little opportunities to participate. The study's goal is to determine whether the Creative Problem Solving learning paradigm may improve the critical thinking abilities and the scientific learning outcomes of Class V students at SD Muhammadiyah Tempirai in the North Penukal District of the PALI Regency. Twenty students were watched and given self-reflection tasks as part of this research. Interviews, questionnaires, and tests were used to compile data on improvements in scientific literacy and critical thinking. The data was analyzed using descriptive statistics. The improvement in markers of learning activities from excellent to very good shows that the CSP learning approach may enhance the efficiency of the learning process. Students' scores on assessments of their critical thinking abilities improved from 77.75 (good) to 81.5 (very excellent), demonstrating that the CSP learning approach is effective in fostering growth in this area.